Membangun Koperasi Pertanian Berbasis Anggota di Era Globalisasi - Susi Widjajani; Siti Noor Hidayati (Jurnal Maksipreneur, 2014)
The purpose of writing this article is to review the development of agricultural cooperatives based members in the globalization. Given the national economic developmentof agricultural development a high priority. And in this agricultural development cooperative strategic role. Agricultural cooperatives is the largest cooperative in Indonesia, but the contribution to the national income is the lowest. Infact, agricultural cooperatives (KUD) actually for med from the top (Government/Employers) and not in bottom of the community. Agricultural cooperatives lost their identity due to the impact of the on going globalization. In such conditions, the need for macro policies conducive to the development of agricultural cooperatives in Indonesia, a complete under standing of the condition of cooperatives, the need for strategic step simprove the internal conditions of the cooperative, and the need for network communication and cooperation with the stakeholders.